Electron beam induced modifications of polyaniline silver nano-composite films: Electrical conductivity and H2S gas sensing studies. (December 2018) - Chaudhary, Nishant; Singh, Ajay; Aswal, D.K.; Jha, P.; Samanta, S.; Chauhan, A.K.; Debnath, A.K.; Acharya, S.; Shah, K.; Muthe, K.P.; Gadkari, S.C.
Abstract: The polyaniline-silver (PANI-Ag) nanocomposite films doped with HCl were prepared on surface modified bi-axially oriented polyethylene teraphthalate (BOPET) by in-situ photo-polymerization. The grown films were modified with high energy (~ 10 MeV) electron beam at different doses (0–100 kGy) in a Linear accelerator. After electron beam exposure the electrical conductivity of the PANI-Ag films was initially found to be enhanced by two orders of magnitude up to 30 kGy of dose and later it falls with increasing dose. Detailed characterizations of the films suggest that enhanced conductivity up to 30 kGy of electron beam dose is due to scissioning as well as additional doping of chlorine in PANI chain, through breaking of covalently bonded chlorine with PANI chain. At higher doses, cross-linking of polymer chains dominates and results in lowering of electrical conductivity. As compared to pristine film, electron beam modified PANI-Ag films exhibit higher sensitivity towards ppm level of H2 S gas. The study highlights the effect of electron beam irradiation on PANI-Ag films in terms of electrical conductivity and its inferences on H2 S gas sensing. Highlights: Synthesis of polyaniline-Ag films through photo-polymerization. Improved electrical conductivity/gas sensing properties of irradiated films. Tailored properties are attributed to enhanced doping and scissioning/crosslinking of PANI chains. Graphical abstract: The electron beam irradiation of PANI-Ag nanocomposite films resulted in tailoring of electrical conductivity and H2 S response due to enhanced doping, scissioning and cross-linking of PANI chains.